1988
DOI: 10.1177/030098588802500602
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis and Copper Accumulation in Skye Terriers

Abstract: Abstract. Livers of nine related Skye terriers with liver disease were evaluated for histological changes and copper content. Lesions ranged from hepatocellular degeneration and necrosis (zone 3) with intracanalicular cholestasis and mild inflammation, to chronic hepatitis with cholangioplasia and cirrhosis. Excess copper (80 1-2,257 pg/g) was related to the severity of cholestasis. Skye terrier hepatitis is a distinct disease entity and may be derived from a disorder of intracellular bile metabolism culminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 10 publications
0
61
0
4
Order By: Relevance
“…10 Hepatic copper concentrations range from 800 to 2,200 g/g dwl (mean, 1,860 g/g), found predominantly in zone 3. Intracanalicular cholestasis is evident on histopathology and is thought to account for the zone 3 copper distribution.…”
Section: Discussionmentioning
confidence: 99%
“…10 Hepatic copper concentrations range from 800 to 2,200 g/g dwl (mean, 1,860 g/g), found predominantly in zone 3. Intracanalicular cholestasis is evident on histopathology and is thought to account for the zone 3 copper distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Copper toxicosis in some dog breeds arouses interest of many scientists due to its specific pathogenesis and numerous similarities to the storage diseases observed in human beings, such as Wilson's disease [2,5]. Up till now the hereditary copper toxicosis has been diagnosed, among others, in Bedlington terriers, Skye terriers, West highland white terriers, Dalmatians, Dobermanns and Retrievers [2,[5][6][7][8][9][10]. Genetic studies in the Bedlington terriers identified COMMD1 gene which plays an important role in copper metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A pattern of fibrosis similar to that in humans frequently occurs in domestic animals [20,25], such as in the case of biliary disease, copper poisoning, pyrrolidine alkaloid poisoning and congestion of the hepatic vein [20,25]. In dogs, copper-associated hepatitis in Bedlington terriers and chronic hepatitis in Doberman pinscher have been reported many times [8,20,27,28,31]. Copper-associated hepatitis is observed as centrilobular hepatocyte necrosis and periacinar fibrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulation of copper and iron observed in the cytoplasm of hepatocytes in some cases has been described in LDH [32]. Although the cytoplasmic accumulation of copper indicates the possibility of copper-related liver disease, copper was not always observed in all samples and the central lobules [3,8,26,27,31].…”
Section: Discussionmentioning
confidence: 99%